2016
DOI: 10.3847/0004-637x/832/2/97
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Model for Spindown of Solar-Type Stars

Abstract: After their formation, stars slow down their rotation rates by the removal of angular momentum from their surfaces, e.g., via stellar winds. Explaining how this rotation of solar-type stars evolves in time is currently an interesting but difficult problem in astrophysics. Despite the complexity of the processes involved, a traditional model, where the removal of angular momentum by magnetic fields is prescribed, has provided a useful framework to understand observational relations between stellar rotation, age… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The magnetic field strength and X-ray activity of solarlike stars increase with rotation rate for slow rotators and then saturate for very fast rotators (Noyes et al 1984;Schrijver & Zwaan 2000;Pizzolato et al 2003;Mamajek & Hillenbrand 2008;Wright et al 2011;Vidotto et al 2014;Reiners, Schüssler & Passegger 2014). Relationships between stellar activity, rotation, and magnetic field strength are all connected to the dynamo origin of these fields within the stars; it is an ongoing enterprise of research to understand these connections and make them quantitative (Karak, Kitchatinov & Choudhuri 2014;Kitchatinov & Olemskoy 2015;Sood, Kim & Hollerbach 2016;Blackman & Owen 2016). In the absence of significant cooling, the winds from solar-like stars, which also draw from the coronal magnetic and thermal energy, are also likely significantly stronger for younger stars.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic field strength and X-ray activity of solarlike stars increase with rotation rate for slow rotators and then saturate for very fast rotators (Noyes et al 1984;Schrijver & Zwaan 2000;Pizzolato et al 2003;Mamajek & Hillenbrand 2008;Wright et al 2011;Vidotto et al 2014;Reiners, Schüssler & Passegger 2014). Relationships between stellar activity, rotation, and magnetic field strength are all connected to the dynamo origin of these fields within the stars; it is an ongoing enterprise of research to understand these connections and make them quantitative (Karak, Kitchatinov & Choudhuri 2014;Kitchatinov & Olemskoy 2015;Sood, Kim & Hollerbach 2016;Blackman & Owen 2016). In the absence of significant cooling, the winds from solar-like stars, which also draw from the coronal magnetic and thermal energy, are also likely significantly stronger for younger stars.…”
Section: Introductionmentioning
confidence: 99%
“…It also dictates the dependence of the angular momentum on the rotation rate and, in practice, it determines how early the effects of braking are felt by a model. Such prescriptions for rotational evolution have a general agreement for young ages up to the solar age (see Sood et al 2016;Amard et al 2016, and references therein), but the evolution for older ages still poses an open question. In particular, van Saders et al (2016) suggested that stars undergo a weakened magnetic braking after they reach a critical value of the Rossby number, thus explaining the stagnation trend observed on the rotational periods of older Kepler stars.…”
Section: Introductionmentioning
confidence: 99%